Viscous flux limiters - Toro, E. F. (Cranfield University, 1991)
We present Numerical Viscosity Functions, or NVFs, for use with Riemann-problem based shock-capturing methods as applied to viscous flows. In particular, viscous flux limiters are derived. The analysis pertain to a linear convection-diffusion model equation. Our NVFs combine the physical viscosity, the role of which is maximised, with numerical viscosity, whose role is minimised, to capture TVD solutions to viscous flows